Rickettsial infections: prevalence and diagnosis of scrub typhus in India - Ravishankar, Vigneshwaran; Narayanan, Shridhar; Shandil, Radha Krishan (Frontiers in Tropical Diseases, 2024)
Rickettsial infections present a substantial public health burden in India. Recent years have witnessed an increase in the incidence of Rickettsial infection-associated morbidity and mortality. These infections are primarily transmitted by vectors such as ticks, fleas, mites, and lice. This review aims to capture epidemiology, diagnosis and emerging disease trends of rickettsial infections, particularly Orientia tsutsugamushi (O. tsutsugamushi) in the Indian context. Diagnosis and treatment of Orientia infections remain challenging due to the lack of sensitive and specific diagnostic tools vis-a-vis clinical treatment in the absence of specific drugs targeting Rickettsial pathogens. Consequently, clinicians often rely on symptoms and epidemiological factors for diagnosis, highlighting the urgent need for improved diagnostics and therapeutic tools. A comprehensive understanding of the epidemiology of rickettsial diseases is essential for formulating effective preventive and control strategies. Identification of high-risk regions and populations by serological and genetic techniques may help the development of targeted interventions. Therefore, enhancing awareness among healthcare professionals and the public regarding epidemiology, clinical features, diagnosis and treatment interventions of rickettsiosis is crucial. This review summarizes the significance of comprehensive epidemiological investigations and diagnostic systems for understanding rickettsial infections in India.